Taurine and tea polyphenols combination ameliorate nonalcoholic steatohepatitis in rats - Wenhua Zhu; Siwen Chen; Ronggui Chen; Zhiqing Peng; Jun Wan; Benyan Wu (BMC, 2017)
Abstract Background Nonalcoholic steatohepatitis (NASH) is a progressive form of nonalcoholic fatty liver disease, for which there is currently no safe and effective drug for therapy. In this study, we explored the effects of taurine, tea polyphenols (TPs), or a combination thereof, on NASH rats. Methods Rats were divided into a normal group, a high-fat diet induced model group and a treatment group (including taurine, TPs, or taurine + TPs treatment for 8 weeks). Twelve weeks later, all rats were sacrificed, and serum transaminase, lipid and lipopolysaccharide levels and hepatic oxidative stress levels were determined. Histological changes were evaluated. Results In NASH rats, hepatocyte damage, lipid disturbance, oxidative stress and elevated lipopolysaccharide levels were confirmed. Taurine treatment alleviated hepatocyte damage and oxidative stress. TPs treatment improved lipid metabolism and increased hepatic antioxidant activity. The therapeutic effects of taurine + TPs treatment on hepatocyte damage, lipid disturbance, and oxidative stress were superior to those of taurine and TPs treatment, respectively. Taurine, TPs and their combination all decreased serum lipopolysaccharide levels in NASH rats, but the combination of the compounds caused these levels to decrease more significantly than taurine or TPs treatment alone. Conclusion Taurine combined with TPs treatment could relieve NASH by alleviating hepatocyte damage, decreasing oxidative stress and improving lipid metabolism and gut flora disturbance partly. Taurine and TPs combination may act as a new effective medicine for treating NASH patients.